Voltage Profile Improvement by STATCOM (International Journal of Engineering and Computer Science, 2014)
The voltage level change in a system due to the drop in the load voltage and change in loads causes the increase in reactive power demand. If that demand not meets by the power system, bus voltage is again decreases. These decrease bus voltage cause the speedy declension of voltage at particular place. This voltage declension of particular place will cause cascading effect on nearby regions, which will further become reason for voltage collapse. In this paper FACTS [1] [2] (Flexible Alternating Current Transmission System) controller such as STATCOM (Static Compensator) is used to operate within the particular voltage limit. STATCOM use in power system for dual purposes such as adsorb the reactive power or to extract the reactive power in transmission line.